Določanje vijačnih lastnosti motorja z merilnimi lističi in osebnim računalnikom v ustaljenih razmerah plovbe ladje - Cvrk, Sead (Strojniški vestnik, 2007)
This paper describes the process of measuring a propeller shaft's elastic deformation by means of a non-contact method, strain gauges and a PC. By usingthe known cross-section as well as the propeller shaft's material type the torque was determined. Knowing the shaft frequency, that is the radial velocity and the torque, it is possible to determine the effective power transmitted from the engine to the propeller. The equipment, i.e., the hardware and the software, was produced by HOTTINGER BALDWIN MESSTEHNIK (HBM),Darmstadt, from the Federal Republic of Germany. The experiment was carried out on a ship belonging to the Navy of Serbia and Montenegro under the conditions of a standard sailing regime.
Keywords: ladijski motorji; dizelski motorji; ladijski vijak; Wheatstonov mostiček